PENDAMPINGAN PENULISAN KARYA ILMIAH BAGI SISWA SMA NEGERI 5 LUBUKLINGGAU - Yeni Asmara; Sarkowi Sarkowi; Supriyanto Supriyanto (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2022)
This community service is motivated by the existence of partner problems in dealing with school accreditation and the lack of student achievement in the field of scientific work, such as the presence of unpublished student scientific work, or the lack of achievements by students in participating in youth scientific work competitions. The methods used in this community service are: 1) Lecture Method; 2) Question and Answer Method; and 3) Simulation Method. The lecture method was chosen to provide explanations and motivate students about the importance of being able to write scientific papers. The question and answer method is very important for the trainees, both when receiving explanations about how to do scientific work and when practicing. This simulation method is very important given to trainees to provide an opportunity to practice the material obtained to determine the level of ability to apply technical scientific writing activities and then identify difficulties (if any) to be solved later. Evaluation of activities is carried out during the process and at the end of the training, on the aspects of achieving the training objectives and also on the implementation of the training. Evaluation of processes and results (achievement of training objectives) is carried out with documentation. Meanwhile, the evaluation of aspects of the implementation of the training is carried out by giving a questionnaire. Indicators of success in the implementation of mentoring for writing scientific papers use 2 methods, namely: (1) Evaluation during the mentoring process, and (2) evaluation after mentoring.